Impact of the Covid-19 Pandemic on the Industry: A Perspective of the Changes Perceived 4 Years After Its Presence - Rosillo, Hector Toledo; Nencheva, Violena (Research Papers, 2025)
The COVID-19 pandemic had an unprecedented impact on businesses, industries, and society. A large number of studies were published after March 2020, documenting both the crisis’s impact on various industries and regions, and exploring the organizational changes and challenges brought by the pandemic. This article examines the changes that many companies had to make in order to adapt in response to the pandemic, in light of the perceived threat and the opportunities arising from it, such as reaching new markets, implementing new lines, or continuing to manage through digital tools.